1996
DOI: 10.1128/iai.64.11.4673-4679.1996
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of outer membrane protein P2 antigenic sites which vary during persistent infection by Haemophilus influenzae

Abstract: Antigenic drift of the major outer membrane protein (MOMP) P2 of nonencapsulated Haemophilus influenzae as observed during persistent infections in patients with chronic bronchitis was mimicked in a rabbit model in which H. influenzae persisted in subcutaneous cages. The antigenic drift resulted from amino acid substitutions in potentially surface-exposed loops of MOMP P2. Since in a rabbit model the appearance of antigenic variants was associated with the presence of strain-specific bactericidal antibodies (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Survival of the population is accomplished by frequent non‐synonymous nucleotide changes within the region encoding the surface‐exposed loop 6. Following the alteration in loop 6 structure, the original antibodies are no longer bactericidal [193]. Interestingly, mutations in this region occur at a significantly higher rate than would be expected by random occurrence.…”
Section: Persistencementioning
confidence: 98%
See 1 more Smart Citation
“…Survival of the population is accomplished by frequent non‐synonymous nucleotide changes within the region encoding the surface‐exposed loop 6. Following the alteration in loop 6 structure, the original antibodies are no longer bactericidal [193]. Interestingly, mutations in this region occur at a significantly higher rate than would be expected by random occurrence.…”
Section: Persistencementioning
confidence: 98%
“…Further analysis has revealed that variation in P2 sequence also occurs within a clonal population during the course of persistent infection. Both in individual children with chronic otitis media and adults with chronic bronchitis due to non‐typable H. influenzae , specific regions of the P2 gene vary at a relatively high frequency [193–195]. These changes correspond to a single surface‐exposed loop referred to as loop 6, which is also the major epitope against which antibodies are targeted.…”
Section: Persistencementioning
confidence: 99%
“…Survival of the population is accomplished by frequent non-synonymous nucleotide changes within the region encoding the surface-exposed loop 6. Following the alteration in loop 6 structure, the original antibodies are no longer bactericidal [193]. Interestingly, mutations in this region occur at a signi¢cantly higher rate than would be expected by random occurrence.…”
Section: Antigenic Drift Of P2mentioning
confidence: 99%
“…The P2 protein is a porin and is strongly immunogenic ). Surface exposed regions of P2 vary greatly in sequence and this antigenic drift allows the organism to evade immune clearance contributing to the development of chronic infection Duim et al, 1996;. Synthetic peptides of these surface exposed regions have also been shown to activate the mitogen-activated protein kinase (MAPK) cascade .…”
Section: Virulence Factors Of H Parasuis and H Influenzaementioning
confidence: 99%
“…The changes are linked to the surfaced-exposed loops of the porin protein and are primarily found in loops 5 and 6. These loops appear at the carboxy terminal end of the protein and the changes have been shown to render the original host antibodies ineffective (Duim et al, 1996). Smith Vaughn et al…”
Section: Antigenic Variationmentioning
confidence: 99%